Second-line monotherapy with a PD-1/CTLA-4 inhibitor effectively treated multiple brain and lung metastases of cervical cancer: a case report - Ni, Juan; Dong, Xiaoyue; Shou, Huafeng; Xu, Qing; Yin, Zhuomin; Lou, Hanmei (Frontiers in Immunology, 2024)
Background Brain metastasis (BM) from cervical cancer (CC) is extremely rare. The prognosis of BM is poor. To our knowledge, no satisfactory therapeutic and standard effective treatments have been established. Immune checkpoint inhibitors (ICIs) treatment is emerging as a promising treatment in recurrence and metastasis(B/M) cervical cancer in recent years. Case We present a 50-year-old patient with CC who developed multiple metastasis (lung, brain and skin) 2 years after postoperative chemoradiotherapy. She received palliative therapy included chemotherapy, resection and stereotactic radiosurgery of BM with poor response. Then, the patient received second-line palliative monotherapy with a PD-1/CTLA-4 inhibitor(cadonilimab) and achieved clinical very good partial response (VGPR), a progression-free survival (PFS) of 14 months and overall survival of more than 18 months since BM. Conclusion We report a case of cervical cancer with multiple metastasis receiving cadonilimab and achieved considerable response and survival benefit.